(untitled) (Agro Productividad, 2024)
O Objective: To analyze the socioeconomic impacts on Valencia orange farming in Martínez de la Torre, Veracruz, Mexico. Methodology: A study was carried out using semi-structured surveys applied to a sample of 40 Valencia orange producers during the 2023 agricultural cycle. Convenience sampling was carried out, considering demographic, agronomic, socioeconomic and environmental variables. The methodology included the analysis of production costs, profits and profitability. A multiple regression analysis was conducted to evaluate the relationships between the variables, using the statistical SPSS software version 29.0. The variables considered were profitability of the crop (dependent variable), and the independent variables: sowing density, age of the crop, yield, and production cost. Results: The coefficients of regression show a direct relationship with the dependent variable, which is why the model as a whole is useful to explain the variability in the profitability of the Valencia orange crop. Conclusions: The current production model highlights key challenges and opportunities for the producers. It is considered that the socioeconomic, agronomic, commercial and environmental variables drive the sustainability and competitiveness of the crop in the region.